Effect of ginger (Zingiber officinale Roscoe) and organic selenium on growth dynamics, blood melanodialdehyde and paraoxonase in broilers exposed to heat stress. Issue 1 (1st January 2019) - Safiullah,; Chand, Naila; Khan, Rifat Ullah; Naz, Shabana; Ahmad, Munib; Gul, Sina
ABSTRACT : A total of 480 1-week-old chicks of about similar average weight, and size were divided into 6 groups. One group served as control, and was fed only basal diet, second group was fed ginger at the rate of 5 g/kg (T1), third group was given organic selenium (Se) at the rate of, 0.3 mg/kg diet (T2), fourth group was given organic Se at the rate of 0.4 mg/kg (T3), fifth group was fed with organic Se at the rate of 0.3 mg/kg + 5 g/kg ginger (T4), sixth group was given organic Se at the rate of 0.4 mg/kg + 5 g/kg ginger (T5). Mean feed intake was significantly ( P  < 0.05) high in T3 and T5 while body weight was significantly ( P  < 0.05) high in T3 compared to the control. Mean feed conversion ratio (FCR) was significantly ( P  < 0.05) high in T2, T3 and T5 compared to the control. Dressing percentage was significantly ( P  < 0.05) high in T4 and T5 compared to the control. Serum Antibody titre against Newcastle disease and paraoxonase (PON1) were significantly ( P  < 0.05) high in the T4 and T5 groups compared to the control while melanodialdehyde (MDA) concentration was significantly ( P  < 0.05) low in the same groups. Results of this study showed that ginger at the rate of 5 g/kg and Se at the rate of 0.4 mg/kg were more effective in improving the growth performance, immune response and antioxidant status in broiler chickens exposed to high ambient temperature.